Portugal and Europe are poliomyelitis free. - Gonçalves, Guilherme; Santos, Luís Almeida; Sarmento, António; Rocha, Graça; Valente, Paula (Acta Médica Portuguesa, 2003)
On the 21st of June 2002, in Copenhagen, the Regional Commission for the Certification of Poliomyelitis Eradication, declared the European Region of the World Health Organization (WHO) as polio-free. The last case (not imported) of poliomyelitis in Europe had occurred in November 1998. The health impact is enormous. In Portugal, the last case of poliomyelitis caused by the wild poliovirus, had occurred in December 1986. The path to eradication in Portugal had begun with a vaccination campaign in 1965/1966, with the oral polio vaccine (Sabin). High vaccination coverage has been maintained since then. The Portuguese program to eliminate poliomyelitis follows the strategic recommendations of WHO, with three components: vaccination; surveillance of acute placid paralysis (AFP); laboratory containment of wild polioviruses. Global eradication has not yet been achieved but is likely to happen till 2005. Keeping the high levels of motivation among Portuguese health workers is essential, in order not to loose what has been achieved. High vaccination coverage has to be maintained. Surveillance of AFP has to be improved and the prompt notification of cases by hospital clinicians, sending stool samples to the reference laboratory, is essential for the success of this activity. The laboratory containment programme is important to prevent the accidental reintroduction of poliomyelitis from laboratories.